A compact wideband circularly polarized antenna with dual SIW cavity modes. Issue 5 (21st January 2020) - Cheng, You‐Feng; Luo, Jie; Peng, Fan; Liao, Cheng
Abstract: This letter presents an improved planar circularly polarized antenna with broad impedance and axial ratio (AR) bandwidths. Four rectangle slots backed by a substrate integrated waveguide (SIW) cavity are fed by a sequentially rotated feeding network to realize the circular polarization. Besides, TE110 and TE210 modes are excited in the SIW cavity and thus an impedance band from 5.24 to 6.44 GHz (20.6%) and an AR band of 5.29 to 6.19 GHz (15.7%) are realized. The antenna also has some other advantages, such as compact size, low profile, and easy integration with other planar circuits, which make it has the potential for some wireless systems.